AYLANMA SUV TA’MINOTI SISTEMASIDA AZOT VA FOSFOR TUTGAN BIRIKMALAR ASOSIDAGI YASHIL KORROZIYA INGIBITORLARINING SAMARADORLIGI (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This thesis analyzes the action mechanisms, efficiency, and environmental advantages of nitrogen- and phosphorus-containing “green” corrosion inhibitors used to protect metal structures in circulating water supply systems (CWSS). It is shown that physicochemical changes resulting from water recirculation, including increased dissolved oxygen, higher salt concentration, and intensified biological contamination, lead to accelerated metal corrosion.